TRADISI PEMBACAAN MAULID BARZANJI PADA MASYARAKAT HULU SUNGAI SELATAN PERSPEKTIF PENDIDIKAN ISLAM (STUDI ETNOGRAFI) - Fuady, M. Noor; Mukaddam, Muhammad Faqih (JURNAL LENTERA [PENDIDIKAN PUSAT PENELITIAN LPPM UM METRO], 2024)
The Barzanji tradition is a tradition of reading Arabic literary works in prose which tells the history of the life of the Prophet Muhammad. some are described in beautiful words, with nuances of praise for the Prophet Muhammad SAW. by Sayyid Ja'far Al-Barzanji which is still implemented by the people of South Kalimantan, especially in the Hulu Sungai Selatan area. The background to the problem of this research is that in society the commemoration of the Prophet's birthday, especially Barzanji, is only a form of ritual, without knowing, understanding and practicing the content and meaning of reading the Barzanji birthday. Meanwhile, the reading of the Barzanji birthday contains a lot of wisdom to be used as a guide in life. The aim of this research is that the researcher wants to describe the implementation of the tradition of reading the Barzanji birthday and the values of Islamic education in the Hulu Sungai Selatan community. This research uses a type of field research which is carried out using a qualitative ethnographic type approach and in descriptive form. Data collection techniques include observation, interviews and documentation. The results of the research include the implementation of the reading of the Barzanji birthday tradition and the values of Islamic education in the Hulu Sungai Selatan community.